The Influence of Financial Literacy and Attitude on Financial Management of MSMEs: A Study on Housewives in Medan Marelan Subdistrict - Kartika Sari Lubis (JUMEBIN : Journal of Management, Economics, Business, and Investment, 2025)
The aim of this research is to determine the influence of Financial Literacy and Financial Attitudes on Financial Management among housewives as MSMEs. The research results show that Financial Literacy has a significant effect on Financial Management, supported by a t-statistic value of 4.626 > t table value of 1.679 and a p-value of 0.000 < 0.05, which means the higher the individual's ability to manage finances. manage finances. Financial Literacy, the greater the individual Financial Management. Financial Attitude has a significant effect on Financial Management, supported by a t-statistic value of 3.363 > t table value of 1.679 and a p-value of 0.001 < 0.05. The results of the coefficient of determination test show that Financial Literacy (X1) and Financial Attitude (X2) contribute to Financial Management (Y) by 0.474 or 47.4%. This study reveals the impact of Financial Literacy and attitudes towards Financial Management in a holistic and comprehensive manner, and provides a valuable new perspective.